Developing a field boundary evaluation and grading system in Ireland - Collier, Marcus (My University, 2003)
The purpose of this study was to develop an evaluation and grading system for the main field boundaries in Ireland – hedgerows and dry stone walls. It is shown that there is a lack of scientific information on Irish field boundaries and very little research has been carried out on what are possibly the most prominent countryside landscape features on the island. In the absence of Irish data, values were extrapolated from research in other countries. In addition, verbal consultation was carried out with prominent landscape ecologists, scientists and environmental consultants. This consultation lead to the creation of a draft survey form modeled on an earlier Hedgerow Evaluation and Grading System (HEGS) (Clements and Tofts, 1992) in the UK. The draft Irish survey, described here, is entitled the Field Boundary Evaluation and Grading System or FBEGS for short. The FBEGS was field-tested in four locations in Ireland by a number of users to obtain usefulness and accuracy. Feedback from volunteer surveyors led to an amended FBEGS survey form. This was then tested in ten locations nation-wide. Results are given and a grading system is proposed. It is shown that it may be possible to evaluate a field boundary using a simple grading system but the accuracy of such a survey cannot be confirmed due to the lack of baseline data in an Irish context. However, preliminary trial surveys indicate that values assigned to a particular boundary approximate well to professional opinion. Discussion concludes with some recommendations for continued research.
Keywords: Dry stone wall; FBEGS; field boundary; hedgerow; landscape management; wallrow